Photoactive carbon monoxide-releasing coordination polymer particles. Issue 71 (17th August 2022) - Carné-Sánchez, Arnau; Ikemura, Shuya; Sakaguchi, Reiko; Craig, Gavin A.; Furukawa, Shuhei
Abstract : The size tunable Mn-based coordination polymer particles demonstrate the controlled carbon monoxide release triggered by light irradiation. Abstract : We report the synthesis of photoactive carbon monoxide-releasing coordination polymer particles through the assembly of Mn(i ) carbonyl complexes with bis(imidazole) ligands. The use of Mn(i ) carbonyl complexes as metallic nodes in the coordination network avoids the potential for aggregation-induced self-quenching, favouring their use in the solid state.